2016
DOI: 10.1016/j.cirpj.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Value-driven product service systems development: Methods and industrial applications

Abstract: In recent times a service-dominant logic is permeating the design of complex systems. However, in spite of their appeal, initiatives such as Product Service Systems (PSS) have not become mainstream, and methods are lacking to support this transition. This paper argues that methodological guidance, as well as tools for decision support, may be found in the research field of Value Driven Design (VDD), which originates in the realm of Systems Engineering. The paper objective is to elaborate on gaps and opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 89 publications
0
38
0
Order By: Relevance
“…Firstly, VDD models do not consider sustainability explicitly, apart from sporadic attempts [221]. Secondly, VDD optimization functions struggle to fit with the earliest innovation process stages, which are characterized by seemingly inconsistent, ill-defined and immature knowledge [222,223].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, VDD models do not consider sustainability explicitly, apart from sporadic attempts [221]. Secondly, VDD optimization functions struggle to fit with the earliest innovation process stages, which are characterized by seemingly inconsistent, ill-defined and immature knowledge [222,223].…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between the lifecycles of the product/service and the interactions/ interdependencies among multiple collaborative networks were studied, namely in the GloNet project [76,88]. The role and importance of collaborative networks in supporting service-enhanced products/product-service systems have attracted considerable research attention in recent years [77,[89][90][91][92]. Tools to exploit user community networks and social media; innovation networks [93,94].…”
Section: Collaboration In Through-engineeringmentioning
confidence: 99%
“…Isaksson et al introduced a value‐driven design methodology based on an information‐driven approach and demonstrated the methodology using an industrial aircraft development case study. Bertoni et al suggested an approach for implementing a value‐driven design to product service systems, and later proposed a value‐driven concept selection method known as early value oriented design exploration with knowledge maturity (EVOKE) . Topcu and Mesmer developed an end‐user value‐based demand model to be used in value‐driven design to maximize value of the system designed.…”
Section: Literature Reviewmentioning
confidence: 99%